Ефективність рекламної кампанії як складової оцінювання комплексної маркетингової діяльності підприємства - Нижник, Л. С.; Nyzhnyk, L. S. (Видавництво Львівської політехніки, 2017)
Охарактеризовано методи визначення ефекту від рекламної кампанії та доведена доцільність їх використання для впливу на рівень обізнаності споживачів про товар на знання та надання переваги, а також комерційного ефекту реклами. Зроблено класифікацію цілей рекламної кампанії залежно від того, до чого прагне організація – інформування цільової аудиторії, переконання споживачів, нагадування про товари та послуги чи укріплення позицій торгової марки. Розглянуто питання визначення оптимального розміру рекламного бюджету в перерізі загальних методів розрахунку бюджету рекламних заходів та п’яти факторів, які потрібно враховувати під час підготовки до складання рекламного бюджету

Now is the time when advertising becomes a science. If you look at advertising as an object, then in its history, advertising has a certain amount of experience, knowledge, discoveries. All this formed several basic laws of advertising, as well as methods and methods of proven and proven life. Advertising, which was once a little predictable, after working out the right approaches to it turned into one of the most reliable types of business. In the current situation of volatile markets and increasing competition, organizations increasingly focus on organizing more effective information flows that accompany the product in all phases of its life cycle. Today it is not enough to make a qualitative competitive product, the most important issue is how to bring out and provide him with strong positions in the market, especially if the market is full of similar goods. Therefore, advertising, as part of marketing, has become one of the main levers of influence on the market. Advertising has become so important in the impact on the turnover of goods that in the West it is surprisingly included in the F. Kotler's complex of the so-called "4P" (Produkt, Price, Place, Promotion). Where advertising refers to promotion, such as personal sales, sales promotion and PR, all of which can be used either for marketing or for attracting attention to goods or services or company ideas. The article presents the results of the study of the dependence of the effectiveness of the advertising campaign on setting goals, strategy and advertising budget. A classification of goals has been made, depending on what the organization seeks to inform the target audience, consumers' persuasion, reminders about goods and services, or strengthening of the brand position. The importance of the "Five M" rule is set at setting goals. The question of determining the optimal size of the advertising budget is considered in the context of general methods of calculating the budget of advertising measures and five factors that should be taken into account when preparing for the construction of an advertising budget, as well as the cost dependence on the product life cycle. Good planning and management of advertising also provides for the assessment of efficiency. First of all, the communicative effect of advertising is determined, that is, its potential impact on consumers' awareness of the product on knowledge and preferences. In addition to the communicative effect of advertisers, it is important to know the commercial effect of advertising. The article examines the methods of determining the effect of advertising and the feasibility of their use. A set of measures for planning an effective advertising campaign is proposed, depending on the setting of goals, strategy and advertising budget. The realities of modern times are such that enterprises are in a state of fierce competition and continuous improvement. And advertising, at this stage, is an indispensable factor in the development and strengthening of enterprises and their brands. Therefore, the question of planning and applying an advertising campaign is an important factor in achieving the goals set. Planning an advertising campaign is a very important and responsible process in the integrated marketing activities of enterprises. And an advertising campaign, conducted in a disparate way with marketing, being autonomous, not related or weakly related to the strategic goals and tactical objectives of the organization's production and market activities, contribute to solving only individual tasks of the organization.
Efficiency of advertising campaign like component of complex marketing activity enterprise assessment
Keywords: рекламна кампанія; реклама; ефект реклами; рекламний бюджет; advertising campaign; advertising budget; strategy; efficiency; planning; goods; services; trade mark; 659.113.7